Evolution of the Lactic Acid Bacterial Community during Malt Whisky Fermentation: a Polyphasic Study - van Beek, Sylvie (American Society for Microbiology, 2002)
The development of the lactic acid bacterial community in a commercial malt whisky fermentation occurred in three broad phases. Initially, bacteria were inhibited by strong yeast growth. Fluorescence microscopy and environmental scanning electron microscopy revealed, in this early stage, both cocci and rods that were at least partly derived from the wort and yeast but also stemmed from the distillery plant. Denaturing gradient gel electrophoresis (DGGE) of partial 16S rRNA genes and sequence analysis revealed cocci related to Streptococcus thermophilus or Saccharococcus thermophilus, Lactobacillus brevis, and Lactobacillus fermentum. The middle phase began 35 to 40 h after yeast inoculation and was characterized by exponential growth of lactobacilli and residual yeast metabolism. Lactobacillus casei or Lactobacillus paracasei, L. fermentum, and Lactobacillus ferintoshensis were detected in samples of fermenting wort examined by DGGE during this stage. Bacterial growth was accompanied by the accumulation of acetic and lactic acids and the metabolism of residual maltooligosaccharides. By 70 h, two new PCR bands were detected on DGGE gels, and the associated bacteria were largely responsible for the final phase of the fermentation. The bacteria were phylogenetically related to Lactobacillus acidophilus and Lactobacillus delbrueckii, and strains similar to the former had previously been recovered from malt whisky fermentations in Japan. These were probably obligately homofermentative bacteria, required malt wort for growth, and could not be cultured on normal laboratory media, such as MRS. Their metabolism during the last 20 to 30 h of fermentation was associated with yeast death and autolysis and further accumulation of lactate but no additional acetate.